2006
DOI: 10.1007/s11524-006-9058-1
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Older Adults in High Impact Volunteering that Enhances Health: Recruitment and Retention in the Experience Corps® Baltimore

Abstract: Engagement in social and generative activities has benefits for the well-being of older adults; hence, methods for broadly engaging them in such activities are desired. Experience Corps Baltimore, a social model for health promotion for older adult volunteers in public schools, offers insight to such successful recruitment and retention. We report on data over a 4-year period in Baltimore City, Maryland, and describe a five-stage screening process implemented to recruit a diverse group of senior volunteers who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 30 publications
1
42
0
1
Order By: Relevance
“…Martinez et al (2006) found that, after the first year of the program, referrals from friends and current volunteers were the best source of recruitment. Tang (2008) found that being asked and seeking out volunteer experiences were the mostly likely ways for older adults to become involved in volunteering.…”
Section: Synthesis Of Best Practicesmentioning
confidence: 99%
See 3 more Smart Citations
“…Martinez et al (2006) found that, after the first year of the program, referrals from friends and current volunteers were the best source of recruitment. Tang (2008) found that being asked and seeking out volunteer experiences were the mostly likely ways for older adults to become involved in volunteering.…”
Section: Synthesis Of Best Practicesmentioning
confidence: 99%
“…Several of the studies indicate that providing opportunities for older adults to participate in activities that are personally meaningful and/or make a difference is an important component in recruiting and retaining older adult volunteers. For example, Martinez et al (2006) suggest that the potential to give back and help children encouraged older adults to engage in volunteer activities. The study by Tang and Morrow-Howell (2008) found that 43% of the volunteers in the study actively sought out volunteer experiences, suggesting that these volunteers were interested in making a meaningful difference in certain areas.…”
Section: Synthesis Of Best Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Volunteers, 60 years and older, were actively recruited 33 to the Experience Corps Baltimore. Eligibility criteria included scoring at least 24 on the Folstein Mini-Mental State Examination 34 and/or meeting a threshold score on Trails B, 35 and passing the school system's criminal background check.…”
Section: Participantsmentioning
confidence: 99%